TAK1 restricts spontaneous NLRP3 activation and cell death to control myeloid proliferation - Malireddi, R K Subbarao; Gurung, Prajwal; Mavuluri, Jayadev; Dasari, Tejasvi Krishna; Klco, Jeffery M; Chi, Hongbo; Kanneganti, Thirumala-Devi (The Journal of experimental medicine, 2018)
The NOD-like receptor (NLR)-P3 inflammasome is a global sensor of infection and stress. Elevated NLRP3 activation levels are associated with human diseases, but the mechanisms controlling NLRP3 inflammasome activation are largely unknown. Here, we show that TGF-β activated kinase-1 (TAK1) is a central regulator of NLRP3 inflammasome activation and spontaneous cell death. Absence of TAK1 in macrophages induced spontaneous activation of the NLRP3 inflammasome without requiring toll-like receptor (TLR) priming and subsequent activating signals, suggesting a distinctive role for TAK1 in maintaining NLRP3 inflammasome homeostasis. Autocrine tumor necrosis factor (TNF) signaling in the absence of TAK1 induced spontaneous RIPK1-dependent NLRP3 inflammasome activation and cell death. We further showed that TAK1 suppressed homeostatic NF-κB and extracellular signal-related kinase (ERK) activation to limit spontaneous TNF production. Moreover, the spontaneous inflammation resulting from TAK1-deficient macrophages drives myeloid proliferation in mice, and was rescued by RIPK1 deficiency. Overall, these studies identify a critical role for TAK1 in maintaining NLRP3 inflammasome quiescence and preserving cellular homeostasis and survival.